2015
DOI: 10.2991/isrme-15.2015.432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on transient behavior of cable-towed acoustic array

Abstract: Abstract. This paper reports on dynamic characteristics of a cable-towed acoustic array system during ship's loop turning maneuvers with a lumped parameter model. The transient behavior of the towed sonar array given rise to the tow-ship's loop maneuvers with different towing speeds, tuning radii, and current are intensively examined via numerical simulation, the corresponding results provide an insight into the tactical aspects of cable-towed array system's applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Their results showed that increasing the towing velocity increases the tension along the cable in the static state. Biao et al 17 modeled the effects of cable tension, rotation radius, and flow on a vessel cable's dynamic behavior during ship rotation movements. The findings indicate that the cable stretching velocity and rotation radius effectively increase or lessen the V deformation of the cable.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that increasing the towing velocity increases the tension along the cable in the static state. Biao et al 17 modeled the effects of cable tension, rotation radius, and flow on a vessel cable's dynamic behavior during ship rotation movements. The findings indicate that the cable stretching velocity and rotation radius effectively increase or lessen the V deformation of the cable.…”
Section: Introductionmentioning
confidence: 99%